The Effect of the Accused’s Absence at the Trial stage- An Analytical and Comparative Study - saeed, zana rafiq; Rashid, Shene Bakr Hama Rashid Hama (Journal of Legal and Political Studies, 2022)
The practical reality made it imperative for the legislator to adopt the idea of a criminal trial in absentia, in the case in which the accused is properly served and fails to appear, the trial stage is guaranteed by a set of guarantees, including the oral procedures, the public hearings and the right to the assistance of a lawyer, and the accused's benefit from these guarantees depends on his presence in the proceedings his failure to attend the trial will inevitably lead to a derogation from these guarantees, and will lead the court to proceed with the case without his presence and to pass judgment on him in absentia. The study was conducted to show the impact of the accused's absence at the trial stage in accordance with the provisions of the Egyptian criminal procedures law in force, which differentiated between the procedures in the in presence and in absentia trial, as well as the difference in the trial in absentia in misdemeanor and violations thereof in felonies, unlike the Iraqi legislator who does not differentiate between procedures in the in presence and absent trial. Keywords :criminal , trial stage, guarantees
Keywords: Keywords criminal; trial stage; guarantees